Selective synthesis of WO3 and W18O49 nanostructures: ligand-free pH-dependent morphology-controlled self-assembly of hierarchical architectures from 1D nanostructure and sunlight-driven photocatalytic degradation - Shirke, Yogita Manikrao; Mukherjee, Shatabdi Porel (CrystEngComm, 2017)
In this study, simple inorganic routes for the synthesis of WO3 and W18O49 nanostructures with variable size and self-assembly are reported. The morphologies and formation of stoichiometric WO3 as well as substoichiometric W18O49 single-crystal phase could be controlled by changing the pH of the reactions medium. This synthesis strategy has the advantages that it is one step, aqueous medium-based, and requires no surfactant or stabilizing agent. Furthermore, it also enables the self-assembly of 1D nanorods of WO3 and W18O49 into hierarchical nanostructures as nanorods bundles, cocoons, urchins, fishbones, etc. This synthesis method may open up a new way to control and tune the stoichiometric and substoichiometric composition of metal oxide nanostructures. Efficient sunlight-driven photocatalytic performance to degrade Rhodamine B (100 mL; 40 mg L-1.) with these tungsten oxide nanostructures was also demonstrated.